2021
DOI: 10.18502/sjms.v16i4.9952
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors Contributing to Nurses’ Intention to Care for COVID-19 Patients Using the Theory of Planned Behavior

Abstract: Background: Globally, the nursing community has lost several colleagues during the Coronavirus Disease 2019 (COVID-19) battle. One of the negative consequences of the disease is the pressure on healthcare services and demands that exceed the system's capacity to provide sufficient resources. Similarly, the experiences of care providers might trigger emotional and physical stress, which could affect the healthcare system's readiness to manage infectious outbreaks. This study was aimed at investigating nurses’ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This trend can be attributed to the two factors. A previous study (Aljohani et al, 2021) In terms of general characteristics, nurses who live with their parents showed a lower intent to provide COVID-19 care. Similarly, Chung et al (2015) also reported that intent to provide care was lower among nurses who live with their families compared with those who live alone.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This trend can be attributed to the two factors. A previous study (Aljohani et al, 2021) In terms of general characteristics, nurses who live with their parents showed a lower intent to provide COVID-19 care. Similarly, Chung et al (2015) also reported that intent to provide care was lower among nurses who live with their families compared with those who live alone.…”
Section: Discussionmentioning
confidence: 70%
“…This trend can be attributed to the two factors. A previous study (Aljohani et al, 2021 ) reported that continuous nursing education that focuses on imparting knowledge about and fostering clinical competency for COVID‐19 care improves nurses' intent to provide care in Saudi Arabia. Considering these results, it can be inferred that nurses' intent to provide care increased owing to the improved COVID‐19 care competency through continuous education and training for infectious disease care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational pressure, stress, and anxiety may drive certain nurses to leave their positions, creating adverse consequences for the healthcare system as a whole. Pressures stemming from emerging infectious diseases prompt nurses in hospital settings to experience fear and apprehension towards their care responsibilities, sometimes causing them to neglect this crucial role [ 6 ].…”
Section: Introductionmentioning
confidence: 99%